In the garden of beasts [compact disc, unabridged] : love, terror, and an American family in Hitler's Berlin - Larson, Erik, 1954- (Random House Audio, 2011)
In 1933, President Roosevelt personally selected William E. Dodd to be the United States ambassador to Nazi Germany. Dodd took his family with him, including his daughter Martha. Initially enamored with the Nazi party and its passion, Martha supported the Third Reich. However, when Hitler's violent policies became apparent, Martha changed her opinion and watched in horror. Here, author Erik Larson offers a chilling first-person account of Germany's transformation under Hitler's rule.